Antimicrobial hydrogel microspheres for protein capture and wound healing. (March 2022) - Lei, Lanjie; Wang, Xiangguo; Zhu, Yulin; Su, Wentao; Lv, Qizhuang; Li, Dong
Graphical abstract: Highlights: Generation of magnetic biohybrid microspheres in a controlled and high throughput manner using microfluidic electrospray technology. Flexible and efficient purification of vascular endothelial growth factor (VEGF) protein from E. coli expression system using magnetic biohybrid microspheres. Induced epithelialization and angiogenesis, and the synergetic antibacterial effects by VEGF-conjugated biohybrid microspheres. Enhanced wound healing in mice using VEGF-conjugated biohybrid microspheres. Abstract: Growth factors are vital to regulate cellular responses for wound healing process. Engineered microspheres provide a promising tool for developing effective growth factor-loaded matrix for regenerative medicine therapy. Here, we report a novel multifunctional chitosan microsphere that enables facile one-step capture and efficient growth factor delivery for enhanced wound repair. The microfluidic technique was used to fabricate magnetic chitosan (MCS) microspheres. By immobilization with Zn 2+ ions, the biohybrid MCS allowed for the flexible operation to capture histidine-tagged vascular endothelial growth factor (VEGF) produced in Escherichia coli (E. coli) . The VEGF-conjugated MCS were then applied onto the wounds to examine their capabilities in promoting wound healing. Zn 2+ and chitosan in MCS exhibited a synergetic antibacterial effect towards both Gram-positive and Gram-negative bacteria. Using a rat model, we further demonstrated that the microspheres significantly promoted wound healing process, as evidenced by rapid wound closure, induced epithelialization and angiogenesis, and reduced inflammation response. Together, our data indicated the presented MCS as a versatile tool for capturing and locally delivering growth factors, which can be applied to wound repair. Moreover, with the functional flexibility, this biohybrid MCS could be empolyed in a wide range of biomedical applications by conjugating proteins of interest.